2016
DOI: 10.1021/acs.jpcc.6b03933
|View full text |Cite
|
Sign up to set email alerts
|

CO Poisoning Effects on FeNC and CNx ORR Catalysts: A Combined Experimental–Computational Study

Abstract: CO poisoning as a probe for oxygen reduction reaction (ORR) active sites was examined on both iron-nitrogen coordinated catalysts supported on carbon (FeNC) and nitrogen-doped carbon nanostructures (CN x ). Rotating disk electrode (RDE) experiments show a partial decrease in the ORR activity of FeNC catalysts after CO exposure and no decrease for CN x catalysts. Diffuse Reflectance Infrared Fourier transform (DRIFT) Spectroscopy experiments after exposure to CO show a peak at 2033 cm -1 (associated with linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 86 publications
(175 reference statements)
3
66
0
Order By: Relevance
“…A possible explanation for this could be that lower concentrations of the halide were employed in these studies, which, according to our calculations for F − and Cl − , could result in only one halide atom binding. The experimental results for CO are likewise inconclusive, with some studies showing no effect, whereas others report a partial decrease in performance . Our calculations suggest that CO would adsorb on one or both sides of the Fe−N 4 motif, depending on the partial pressure, and this would lead to a reduced limiting potential or poisoning, respectively.…”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…A possible explanation for this could be that lower concentrations of the halide were employed in these studies, which, according to our calculations for F − and Cl − , could result in only one halide atom binding. The experimental results for CO are likewise inconclusive, with some studies showing no effect, whereas others report a partial decrease in performance . Our calculations suggest that CO would adsorb on one or both sides of the Fe−N 4 motif, depending on the partial pressure, and this would lead to a reduced limiting potential or poisoning, respectively.…”
Section: Resultsmentioning
confidence: 60%
“…It is of interest to compare our results with experiments reported in the literature, keeping in mind the variation in catalyst preparation and poisoning procedures across these studies. An experiment comparing the activities of M−N/C catalysts with M=Mn, Fe, and Co found that they followed the order Fe>Co>Mn; the half‐wave potentials of the three metals differed by 0.08 V. To match this observation with theoretical calculations, Zelenay et al.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations